Applicability of Socio-Technical Model (STM) in Working System of Modern Organizations - Tasmin, Rosmaini; Che Rusuli, Muhamad Saufi (Journal of Techno-Social, 2010)
Knowledge has been identified as one of the most important resources in organization that contributes to competitive advantages. Organizations around the world realize and put into practice an approach that bases on technological and sociological aspects to fill-up the gaps in their workplaces. The Socio-Technical Model (STM) is an established organizational model introduced by Trist since 1960s at Tavistock Institute, London. It relates two most common components exist in all organizations, namely social systems (human) and technological systems (information technology, machinery and equipment) in organizations over many decades. This paper reviews the socio-technical model from various perspectives of its developmental stages and ideas written by researchers. Therefore, several literature reviews on socio-technical model have been compiled and discussed to justify whether its basic argument matches with required practices in Techno-Social environments. Through a socio-technical perspective on Knowledge Management, this paper highlights the interplay between social systems and technological system. It also suggests that management and leadership play critical roles in establishing the techno-social perspective for the effective assimilation of Knowledge Management practices.